Making Economically Valuable Compost Fertilizer from Organic Waste Management in Margaluyu Village - Purnamasari, Dini; Fitriana, Maulia Nashwa; Optapiani, Sipani Auliya; Salsabila, Claudia; Ramadana, Ara Awalia; Nugroho, Auliya Fathihatunnisa; Fibriyani, Zahra (Jurnal Pengabdian West Science, 2026)
Waste sorting is useful for reducing the negative impacts of household waste, creating a clean and comfortable environment, and fostering collective awareness of maintaining cleanliness. Effective waste management, resulting in a marketable value, positively impacts the social and economic conditions of the community. This community service activity was conducted in Margaluyu Village, Kasemen, Serang. This community service activity aims to educate the community in the village so they can sort waste for reuse and use it as compost, which has economic value for the community.